Effect of Ascorbic Acid and Yeast Strain on Sauvignon blanc Wine Quality - Swart, E.; Marais, J.; Britz, T.J. (South African Journal of Enology and Viticulture, 2017)
Sauvignon blanc cultivar-typical aroma is affected by different components of which 2-methoxy-3-isobutylpyrazine and 4-mercapto-4-methylpentan-2-one are probably the most important. Climatic, viticultural and oenological conditions may have a prominent effect on the levels at which these impact aroma components occur in wine.  Sauvignon blanc wines were produced from grapes from two climatically different regions. Different ascorbic acid/S02 combinations and different Saccharomyces cerevisiae yeast strains were used during the production of the wines. The wines were sensorially evaluated for specific wine characteristics, namely fruity/ester aroma intensity, grassy/green pepper aroma intensity, sulphur-like aroma intensity and overall wine quality.  Significant differences were observed between treatments. A commercially available preparate (ascorbic acid/meta-bisulphite) and yeast strain VL3C produced sulphur-like, low-quality wines under the conditions of this investigation. The highest quality wines were produced from pure ascorbic acid/S02 treatments and fermentation by the yeast strain VIN 13.